The leadership role of Chairmen in bank management - Adewunmi, Wole (Lagos, Nigeria: Chartered Institute of Bankers, 1992)
The book educates board men and women on their functions, roles and responsibilities as bank managers.
rua 25/11/16
Loans
Keywords: Bank management; Banks and banking; Bank management - leadership; Nigeria